2005
DOI: 10.1038/sj.pcan.4500840
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the prostate-specific antigen gene promoter do not predict serum prostate-specific antigen levels in African-American men

Abstract: A major problem with the use of serum prostate-specific antigen (PSA) in predicting prostate cancer risk is the considerable variability of such measurements. Cramer et al. identified a set of singlenucleotide polymorphisms (SNPs) in the upstream regulatory region of the PSA gene that were each associated with increased promoter activity and serum PSA, further suggesting that genotyping these SNPs could be useful in improving the predictive value of PSA screening. In order to replicate this finding, DNA sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
2
8
1
Order By: Relevance
“…The haplotype -5429 G/-5412 C/-4643 G was shown to occur in 20% of the population and was found to be associated with increased serum PSA levels. By contrast, a study by Beebe-dimmer et al (23) we did not observe a statistically significant difference in the serum PSA levels of prostate cancer patients or controls with the heterozygous genotype compared to those with the homozygous genotype. The expression of PSA is not exclusively controlled by the enhancer region; functional SNPs present in the proximal promoter region may also exert an effect on expression levels.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The haplotype -5429 G/-5412 C/-4643 G was shown to occur in 20% of the population and was found to be associated with increased serum PSA levels. By contrast, a study by Beebe-dimmer et al (23) we did not observe a statistically significant difference in the serum PSA levels of prostate cancer patients or controls with the heterozygous genotype compared to those with the homozygous genotype. The expression of PSA is not exclusively controlled by the enhancer region; functional SNPs present in the proximal promoter region may also exert an effect on expression levels.…”
Section: Discussioncontrasting
confidence: 54%
“…association with serum PSA levels and the risk of prostate cancer (22,23). Cramer et al were the first to identify polymorphisms in the 5' promoter region of the PSA gene and to analyze their association with serum PSA levels (22).…”
Section: Discussionmentioning
confidence: 99%
“…However, the results largely remain inconsistent Burmester et al 2004;Beebe-Dimmer et al 2006;Severi et al 2006). Cramer et al (2003) had reported signiWcant association of three variants in the promoter of the PSA gene (KLK3) with higher serum PSA levels in Caucasian men without prostatic disease.…”
Section: Discussionmentioning
confidence: 98%
“…All of these observations strongly implicate both KLK3 and KLK2 as plausible candidate genes involved in prostate cancer susceptibility. However, previously reported associations of upstream variants in KLK3 with serum PSA levels have remained inconclusive Beebe-Dimmer et al 2006). Using a set of single nucleotide polymorphisms (SNPs) that span the KLK2 region, Nam et al (2006) have demonstrated that KLK2 variants correlate with hK2 serum levels and are predictive of prostate cancer susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…Several SNPs in the KLK3 promoter were reported to be associated with serum PSA levels (19, 20), and one was associated with prostate cancer risk (35), but later studies failed to confirm these associations (21, 3639). In an earlier study of the same cohort, we found that a KLK3 promoter SNP, rs266882, in combination with androgen receptor gene CAG repeat length, was significantly associated with serum levels of tPSA (38).…”
Section: Discussionmentioning
confidence: 99%